(untitled) (Ameghiniana, 2017)
At the eastern margin of the Precordillera and close to the boundary with Sierras Pampeanas, the Rinconada Formation displays extensional faults, boudinaged sequences and scarce slump folds for which age is not well constrained. It represents a stacking of “broken formations” intercalated with scarce debris flows. A calcareous iron-rich sample from the upper levels of the Rinconada Formation yielded 134 conodont elements, including Dapsilodus obliquicostatus, Decoriconus fragilis, Oulodus sp., Pseudooneotodus beckmanni, P. b. bicornis and Wurmiella excavata together with ozarkodinids of the “Oz.” bohemica–“Oz.” snajdri lineage. The record of “Oz.” aff. snajdri suggests a late Homerian–early Gorstian (late Wenlock–early Ludlow) minimum depositional age for the upper debris flows of the Rinconada Formation. The studied conodont fauna improves the biostratigraphic correlation of the Rinconada melange with other successions in the Precordillera and the world as well as provides clues on the tectonostratigraphic development of the SW Gondwanan foreland during Silurian times. Resumen. CONODONTES SILÚRICOS DE LA FORMACIÓN RINCONADA, PRECORDILLERA ARGENTINA. La Formación Rinconada, situada en el margen oriental de la Precordillera y próxima al límite con las Sierras Pampeanas, muestra fallas extensionales, así como pliegues y budines originados por deformación de sedimentos no litificados. Esta formación, cuya edad no ha sido bien precisada, está constituida por un apilamiento de “formaciones rotas” intercaladas con escasos flujos de detritos. Una muestra calcárea rica en hierro de los niveles superiores de la Formación Rinconada brindó 134 conodontes, incluyendo Dapsilodus obliquicostatus, Decoriconus fragilis, Oulodus sp., Pseudooneotodus beckmanni, P. b. bicornis, Wurmiella excavata y ozarkodínidos del linaje “Oz.” bohemica– “Oz.” snajdri. El registro de “Oz.” aff. snajdri permite sugerir una edad mí- nima depositacional Homeriana tardía–Gorstiana temprana (Wenlock tardío–Ludlow temprano) para los flujos de detritos del tramo superior de la Formación Rinconada. La fauna de conodontes recuperada de la Formación Rinconada favorece la correlación estratigráfica con otras sucesiones sedimentarias de la Precordillera y del mundo, así como brinda claves sobre el desarrollo tectonoestratigráfico del antepaís del suroeste de Gondwana en tiempos silúricos.